Internalisasi Karakter Religius dalam Pembelajaran Bahasa Arab - Harahap, Putri Hasanah; S, Sapri; Harahap, Wafi; Rangkuti, Luthfiyah Hayati; AlFitriyani, Nuri; Hasana, Tri Fauziah; Brutu, Sabilla Meliani; Sitompul, Buti Sarma (Madani: Jurnal Ilmiah Multidisiplin, 2024)
At MI schools there is Arabic-based learning which aims to enable children to know Arabic. Apart from language learning, students can also internalize religious character education. To achieve this, all teachers and schools have a role and effort in it. So the aim of our research is how teachers can make children internalize religious character education in learning Arabic. This writing uses a qualitative approach method, namely by collecting library data, reading, taking notes and discussing our discussion material. So the results of the research we conducted are teachers' efforts to help students, including: Using religious texts in learning Arabic such as the Koran or hadith, Teachers integrating religious values into the context of teaching Arabic, Teachers forming ethical discussions that involves values. -religious values in the classroom, the teacher must also be a good example in applying religious character in Arabic language learning and the teacher helps students to understand the meaning and religious values in the Arabic texts they study.